Pengaruh Pemberian Silase Pakan Komplit Berbasis Sorgum-Clitoria Ternatea Dengan Penambahan Konsentrat Mengandung ZnSO4 Dan ZnCu Isoleusinat Terhadap Kadar Metabolit Darah Kambing Kacang - Nubatonis, Imron Alberto; Hartati, Erna; Lestari, Gusti A. Y.; Nenobais, Mariana (Animal Agricultura, 2024)
The aim of this research was to determine the effect of providing complete feed silage based on sorghum-Clitoria ternatea with the addition of concentrate containing ZnSO4 and Zn-Cu isoleucinate on the blood metabolites of Kacang goats.  This research used 12 Kacang goats aged 12 months with an average body weight of 13.21 kg (KV=14.01%).  This research used an experimental method with a randomized block design (RAK) with 4 treatments and 3 replications.  The four treatments are T0: sorghum-Clitoria ternatea silage without concentrate, T1: complete feed silage containing 10% concentrate, T2: complete feed silage containing 20% concentrate, and T3: complete feed silage containing 30% concentrate, each treatment contains  150 ZnSO4 kg concentrate and Zn-Cu kg Isoleucinate ration.  The results of this study showed that giving complete feed silage with the addition of concentrate containing ZnSO4 and Zn-Cu isoleucinate did not have a significant effect (P>0.05) on cholesterol levels, glucose levels, total plasma protein levels and blood urea levels in Kacang goats.  In conclusion, giving complete feed silage based on sorghum-Clitoria ternatea with the addition of concentrate containing ZnSO4 and Zn-Cu isoleucinate does not affect cholesterol levels, glucose levels, total plasma protein levels and blood urea levels in Kacang goats.